Neutron emission studies from miniature and medium size plasma focus device - Singh, Rajdeep Raweet. (2010)
Although dense plasma focus devices have attracted the attention of scientific community since 1960’s as a copious source of fusion neutrons but in the recent years owing to spin-off in the applications of compact and portable table top neutron sources in wider domain, like noninvasive interrogation of explosives and narcotic drugs (by using Pulsed Fast/Thermal Neutron Analysis (PFTNA) technique), dark matter research, radioisotope production, medical neutron therapy and soil humidity measurements, there has been renewed interest across the globe for the development of sub-kilojoule range, low energy small plasma focus device (hereafter called ‘Miniature Plasma Focus i.e. MPF) ) based pulsed neutron sources. Since the low energy MPF devices are compact, inexpensive, long lasting and easier to maintain; these distinctive features sets them apart from other sources as a prime candidate for compact pulsed neutron source. From the perspective of being utilized as a non-intrusive and non-destructive scanning tool, the added advantage with plasma focus devices is also that hard X-Ray and neutron scanning can be done simultaneously as the emission of neutrons is always accompanied by hard X-Rays.